Design and synthesis of an orally active biologic based on cyclic ω-conotoxin MVIIA-GS. - Koh, Samantha Qian Ping. (2011)
MVIIA is a peptide isolated from cone snail venom. It is a potent inhibitor of N-type voltage-gated calcium channels on presynaptic neurons, preventing release of neurotransmitters for pain signal transmission. Its synthetic form Ziconotide has been approved for clinical therapy but can only be administered intrathecally, which causes undesired side effects. This study aims to synthesize orally active analgesic by cyclizing MVIIA with a GS linker. Cyclic MVIIA-GS exhibited high thermal, chemical and enzymatic stability found in cyclotides with a similar cysteine knot structure. MVIIA-GS gene was designed and cloned into pTxB1 vector to express MVIIA-GS–Intein–CBD fusion protein, which was purified by affinity chitin column. Intein-mediated cleavage and cyclization of MVIIA-GS was examined after 4days. Cyclic MVIIA-GS was purified by RP-HPLC, where it eluted from 30% to 32% acetonitrile. Folded, cyclic MVIIA-GS was eluted as part of a cluster from 20% to 30% acetonitrile. The biosynthesis approach used in this study was able to synthesize fully-folded cyclic analogue of native MVIIA. However, its yield of native-fold cyclic products with complicated cystine knot structure was limited. More research to optimize the synthesis process, verify the identity of the synthetic product and to test its biological activities is needed.